EVALUATION OF THE USABILITY OF SMART APPS CREATOR 3.0 AS AN AUTHORING TOOL FOR THE DEVELOPMENT OF DIGITAL LEARNING MEDIA FOR TEACHERS - Ferdiansyah, Dito (EDUCATE : Jurnal Teknologi Pendidikan, 2026)
Smart Apps Creator (SAC) 3.0 is an authoring tool widely used by teachers to develop digital learning media. Despite its increasing adoption, empirical evaluations of its usability remain limited. This study aimed to evaluate the usability of Smart Apps Creator 3.0 as an authoring tool for developing digital learning media by teachers. A quantitative approach with a descriptive research design was employed. The usability evaluation was conducted using the System Usability Scale (SUS) involving 30 teachers as respondents. The data were analyzed by calculating SUS scores and interpreting the results based on the established SUS interpretation framework. The findings indicate that Smart Apps Creator 3.0 achieved a SUS score of 67.91, which falls within the Marginal High category, indicating that the system demonstrates a level of usability close to the acceptable threshold, although several aspects still require improvement. Item-level analysis revealed that ease of use and user confidence were perceived positively, whereas learnability and the need for technical support remain the primary challenges. These findings demonstrate that Smart Apps Creator 3.0 provides an adequate level of usability while offering an empirical baseline for future system improvement and related research